Development of the pediatric narcolepsy patient-reported outcomes scale (PN-PROs) - Wang, Grace Y.; Worhach, Jennifer; Zhou, Eric S.; Strunc, Michael; Morse, Anne M.; Owens, Judith A.; Flygare, Julie; Revette, Anna; Meltzer, Lisa J.; Maski, Kiran (Frontiers in Sleep, 2024)
Background: Pediatric narcolepsy is a chronic neurological disorder that impacts the health and overall well-being of children and adolescents with the disease. Meaningful and regular assessment of symptom frequency and severity is important for the long-term management of narcolepsy and for optimizing quality of life. However, there is currently no patient-reported outcomes (PROs) measure developed from both patient and expert input that is designed specifically to assess the impact of pediatric narcolepsy on daily life and overall disease burden. Methods: We conducted a qualitative mixed-methods study to develop a novel patient-reported outcomes measure for pediatric narcolepsy patients. We created and refined a conceptual framework through literature review, semi-structured interviews with narcolepsy experts, and focus groups of children and adolescents with narcolepsy and their parents. Guided by the domains and facets identified in our conceptual framework and further literature review, we developed a PROs item bank. Our team further refined the item bank and classified items through team discussions and expert guidance. Content validity of the item pool was evaluated with expert review, readability analysis, and cognitive interviews with narcolepsy patients. Results: Through our processes, we developed a PROs item bank comprising 2 domains (narcolepsy symptoms and functional impairment) that contains 10 facets. The final item bank consists of 55 items, with 27 items representing 5 facets of narcolepsy symptoms (behavior, cataplexy, cognitive difficulties, sleep quality, and sleepiness) and 28 items representing 5 facets of functional impairment (bothered by/worried about symptom, cognitive/academic, global functioning, safety, and social). Conclusion: We developed items for the Pediatric Narcolepsy Patient-Reported Outcomes (PN-PROs) measure that incorporates expert insight, published literature, and testimony from children/adolescents living with narcolepsy and their families. Upon completion of the psychometric testing and content validation process, we believe the PN-PROs will provide a useful longitudinal measure of disease control and standardize outcome assessments in clinical practice and research studies.